Characterization of a Geopolymer Foam by X-ray Tomography - Petlitckaia, Svetlana; Vincente, Jérôme; Poulesquen, Arnaud (Frontiers in Chemistry, 2021)
Metakaolin based geopolymer foams were synthesized at room temperature by direct foaming using hydrogen peroxide (H2O2) as a blowing agent and two types of surfactants such as AER5 and CTAB allowing to tune the connection between two adjacent cells. In the field of decontamination process of liquid wastes, the knowledge of the topology of the generated macroporous network is a primary of interest. Due to the complex structure of porous material, 2D conventional techniques as optical or scanning electron microscopy are often not able to provide all the necessary informations. The 3D networks were therefore characterized by X-ray tomography to determine the morphological structure parameters that is useful to manufacture geopolymer material for filtration applications. The porosity, the pore size distribution and constriction between adjacent cells, as well as the connection rates between pores were analyzed by the iMorph program. The results show that the total porosity increases from 26 to 74% when the initial concentration of H2O2 increases, which is in complete agreement with the tomography results. Materials synthetized from CTAB surfactant are poorly connected whereas those generated from AER5 surfactant have a higher mean cell size (at equivalent initial H2O2 concentration) and are fully connected, which will facilitate the transport of fluid through the material. These features have a strong impact on the value of permeability coefficients of the geopolymer foams. Indeed, permeabilities calculated from a Pore Network Modeling (PNM) approach or Kozeny-Carman equation, are ranged in between 10-14 to 10-10 m² depending on the cell connectivity, the throat size and the total porosity.